Physical-mechanical properties of laminated bamboo panels - Fernando Rusch; Rômulo Trevisan; Éverton Hillig; Erick Chagas Mustefaga (Pesquisa Agropecuária Tropical, 2019)
Bamboo is a material used on a global scale in several areas. However, it needs adaptation in the processes for industrial use, in Brazil. The production of glued laminated panels has been growing in the world and this material can be a source of resources for this purpose. This study aimed to evaluate the physical-mechanical properties of laminated bamboo panels produced with two species (Phyllostachys aurea and Dendrocalamus asper) and two production processes/adhesives (glued-laminated bamboo and thermo-mechanical laminated bamboo). For the mechanical properties analysis, specimens removed from the panels were subjected to shear tests, Janka hardness and static bending. The same specimens were used to determine the apparent density, moisture content and degree of compression. The apparent density varied between 0.75 g cm-3 and 0.79 g cm-3, with equilibrium moisture contents between 7.83 % and 10.42 %. The highest values for the mechanical properties were verified in the thermo-mechanical laminated process. For D. asper, the modulus of rupture was 146.8 MPa, the shear glued line 6.36 MPa and the Janka hardness 3,852 N, while, for P. aurea, the modulus of elasticity reached 19,603 MPa. It was concluded that the production of bamboo laminated panels, especially using the thermo-mechanical process, can be a potential alternative.